Profile and Perception of Pregnant Women Towards Syphilis Infection Pregnancy - Rustikayanti, R. Nety; Jayanti, Tri Nur; Dirgahayu, Inggrid (Indonesian Journal of Global Health Research, 2024)
The number of cases of pregnancy syphilis infection at the Ibrahim Adjie Community Health Center has increased in recent years. Until now, not all cases have been found and it is estimated that this will be greater than the current findings. The response of pregnant women to the diagnosis of syphilis infection tends not to be interpreted as a disease that can affect pregnancy. One of these conditions is related to the mother's perception of syphilis infection during pregnancy. Researchers have not yet obtained studies related to risk factors and perceptions, especially in Indonesia. Objective: This research was conducted to obtain risk factors related to pregnant women's perceptions of pregnancy syphilis infection. Method: Research variables include maternal age, occupation, income, ethnicity, gravida status, gestational age, sex, and perception. The research instrument consists of demographic data and a questionnaire with an alpha value of 0.939. Data collection using a survey approach uses primary data. Results: The results of the analysis showed that the highest percentage was in the age category of more than 19 years (90.9%), housewife (81.8%), multigravida (65.5%), gestational age more than 28 weeks (45.5%), sexual risk (54.4%), perception supports (65.5%), and the correlation value with Spearman is 0.361. Conclusions: Supportive perceptions provide the same contribution to risky and non-risky sexual activity, whereas risky and non-risky sexual activity produces supportive perceptions. The respondent's perception that the perspective on pregnancy syphilis does not arise due to previous sexual experience can be caused by other factors that contribute both internally and externally.